Insight Into the Leaching of Sodium Alumino-Silicate Hydrate (N-A-S-H) Gel: A Molecular Dynamics Study - Wan, Hongyan; Yuan, Liqun; Zhang, Yu (Frontiers in Materials, 2020)
This paper provides an intrinsic mechanism of alkalis dissolution from the gels of geopolymer at nanoscale, via a molecular dynamics (MD) investigation on N-A-S-H gel, the predominant binding phase in geopolymer. Sodium plays roles in balancing charges of [AlO4] tetrahedron, and its absence causes local structure to show negative charge, resulting in locally mutual repelling between tetrahedrons. Also, sodium dissociation promotes hydrolytic reaction, exacerbating non-conservation of charge of the N-A-S-H system, further swelling the structure. Above evolution weakens the alumino-silicate skeleton and reduces the stability of silicate and aluminate species, which in turn promotes sodium dissociation. In the long term, it increases the potential of structure depolymerization and even peeling off. Based on previously reported experiments and our computational results, it is presumably that leaching starts from N-A-S-H substrate surface, and the gel peels off layer by layer in the above manner, resulting in microscopic holes and fissures. In addition, leaching also leads to the degradation of mechanical properties of surface gel, including Young`s modulus, tensile strength, and ductility, which considerably increases the possibility of surface gel peeling. Besides, sodium is able to connect [AlO4] and [SiO4] tetrahedrons by the electrostatic force with tetrahedral oxygen, which transfers stress and contributes to uniform stress dispersion.